Power Factor Correction in Two Leg Inverter Fed BLDC Drive Using Cuk Dc-Dc Converter - A. Purna Chandra Rao; Y.P. Obulesh; Ch. Sai Babu (Institute of Advanced Engineering and Science, 2015)
Earlier for variable speed application conventional motors were used, but these motors have poor characteristics. These drawbacks were overcome by brushless Dc motor drive. Now days in most of the applications such as industrial, domestic, aerospace, defense, medical and traction etc, brushless DC motor (BLDCM) is popular for its high efficiency, high torque to weight ratio, small size, and high reliability, ease of control and low maintenance etc. BLDC motor is a electronic commutator driven drive i.e. it uses a three-phase voltage source inverter for its operation, electronic devices means there is a problem of poor power quality, more torque ripple and speed fluctuations. This paper deals with the CUK converter two leg inverter fed BLDCM drive in closed loop operation. The proposed control strategy on CUK converter two leg inverter fed BLDCM drive with split DC source is modeled and implemented using MATLAB / Simulink. The proposed method improves the efficiency of the drive system with Power factor correction feature in wide range of the speed control, less torque ripple and smooth speed control.